THE INFLUENCE OF ATTRACTIVENESS AND PRICE ON CONSUMER PURCHASING DECISIONS AT PT. MATAHARI DEPARTMENT STORE THAMRIN PLAZA BRANCH: PENGARUH DAYA TARIK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PT. MATAHARI DEPARTEMENT STORE CABANG THAMRIN PLAZA - Syahri, T. Alfi (UPMI Proceeding Series, 2023)
The purpose of this study was to test and analyze the effect of attractiveness, price partially and together on consumer purchasing decisions at Matahari Department Store Thamrin Plaza Branch. This type of research is explanatory research. The population of this study were consumers of Matahari Department Store Thamrin Plaza Branch with a total population of 950. Based on the calculation of the number of samples based on the slovin formula, the minimum number of samples to be submitted is at least 95 samples. Data collection techniques in this research used observation, documentation and questionnaires. Based on the results of the study, it was obtained that the significance value of attractiveness on purchasing decisions based on the t test was obtained at tcount > ttable (2.323 > 1.985) (Sig 0.022 <α0.05). In conclusion: there is a significant effect of attractiveness on product purchasing decisions at Matahari Department Store Thamrin Plaza Branch. From the results of this study, it was obtained that the price significance value based on the t test was obtained for tcount > ttable (6.851 <1.985) (Sig 0.000 <α0.05) in conclusion: there is a significant effect of price on purchasing decisions at Matahari Department Store Thamrin Plaza Branch. Based on the results of the F test, it was obtained that the value of Fcount > Ftable was (24.342 > 3.10) (Sig. 0.000 <α0.05) in conclusion: there is a significant influence of attractiveness and price on product purchasing decisions at Matahari Department Store Thamrin Plaza Branch.